Characteristic Performance of Deionized Columns - D. Al-Sabti, Matheel; W. Kasser, Nahidh; Y. Hussein, Mudhafar (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
The reclamation of makeup water is studied in terms of breakthrough time (i.e., the leakage of the cations). Makeup water was subjected to lab-scale ion exchangers of two types: strong acid cation and weak base anion exchanger. The experimental investigation was directed to study the ion exchanger performance in terms of four different parameters (i.e., copper concentration, total dissolved solids (TDS), feed rate and bed depth). Box-Wilson composite rotatable design was adopted in designing the experiments. Breakthrough times of the effluent stream are measured in terms of copper concentration of 2 to 25 ppm, TDS concentration of 250 to 1250 ppm, feed rate of 0.38 to 5.34 l/h and bed depth of 5 to 70 cm. Simulation the effect of the studied variables through their pre-designed ranges in terms of breakthrough time was done by 2nd order polynomial equation. In general, the performance and characteristic of adopting two bed deionizers (cation and anion beds) was efficiently recommended to remove the ionic contaminants and not less than 95 % of wastewater is recycled.